DIMENSI METAFISIK SÃRAT WIRID HIDAYAT JATI: RELEVANSINYA BAGI PEMBANGUNAN KARAKTER BANGSA - , Reno Wikandaru, Prof. Dr. Joko Siswanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study entitled Metaphysical Dimensions of Sêrat Wirid Hidayat Jati: Its Relevance For Nation Character Development is motivated by the weakness of both national identity and commitment to the nationâs personality in the globalization era which then makes the values of foreign cultures can easily fit in people's lives without going through the filtration process first. As a result, local cultural values be abandoned, and can be easily replaced by the values of pop culture (popular). The main objective of this research is to find a philosophical thinking in the local wisdom, in this case is Sêrat Wirid Hidayat Jati, especially regarding the metaphysical dimension that is in it, so that can be used as a reference in the nation character building efforts in the era of globalization. This research is a library research that uses a model of factual-historical research about the text or manuscript. Material object in this research is Sêrat Wirid Hidayat Jati, while the formal object that is used as an analytical tool is metaphysics. The methodical elements used is description, historical, language analytics, abstraction, hermeneutics, and heuristics. Results obtained in this study were (1) philosophical thinking which can be found in these works is about man, God, nature, and a little about morality, (2) there are five metaphysical dimensions contained in Sêrat Wirid Hidayat Jati. First, the quantity of reality dimension is characterized by monistic, namely the Essence of God, which is became the first principle or foundation of the existence of all sections of this reality (the divine view of pantheism). Second, the quality of reality dimension, which is about the spiritual nature of the Essence of God as the ultimate nature of reality, which then had tajalli or manifested into the seven Dignity. Third, the dimension of reality dynamics, namely the God who has no beginning and no end, creation as the God's activities, Seven Dignity as the development of God, and Sangkan Paraning Dumadi as the dynamics law of reality. Fourth, the dimension of realityâs goal, namely the doctrine of Manunggaling Kawula lan Gusti as the final or ultimate goal of reality. Fifth, the dimension of ontological-transcendental norms that is about the nature of God (Kodrat). (3) The relevance of the metaphysical dimension of Sêrat Wirid Hidayat Jatiwith the nation character development is: first, the dimensions of quantity and quality reality in Sêrat Wirid Hidayat Jati relevant to the issue of spirituality crisis, secondly, the dimension quality of reality and dynamics of reality in Sêrat Wirid Hidayat Jatirelevant to the issue of pragmatism lifestyle, and thirdly, the dimension of realityâs goal in Sêrat Wirid Hidayat Jati relevant to the development of awareness about life.